Peningkatan Sumber Daya Manusia Berbasis TIK dan Literasi Digital melalui Pelatihan TIK Bagi Masyarakat Distrik Nimboran - Ermy Dikta Sumanik; Reni Koibur; Fegie Y Wattimena; Axelon S Renyaan; Yoga Erwanto; Joice Y Kabagaimu; Oktovianus A Bwefar (Yayasan Kawanad, 2022)
Improving human resources in the field of ICT and digital literacy for village officials is very important in this digital era. The lack of skills in operating ICT has hampered in operating Ms. Office and google. The purpose of this training activity is to increase the capacity of human resources in the field of ICT and digital literacy in the community of Nimboran district. The method used in this activity is direct training and mentoring. This ICT activity was carried out for three days of training. At the beginning of the activity, it was distributed to measure participants' understanding in operating Ms. Office and Google. Monitoring and evaluation is done by presenting the post-test directly. The result of this ICT training is 72,61%have been able to improve their competence in operating Ms. Office and Google.